Perspective of SME’s: Assessing the Profound Impact of Big Establishments on Small and Medium Enterprises (SME’s) at Poblacion, Mandaon, Masbate - Sabaulan, Jelyn C.; Aguilar, Teresa A.; Villester, Sharmaena M.; Desales, Regane B.; Badiana, Karla Mae G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The operation of SMEs produces a large share of employ-ment and income generation, and they are essential in distrib-uting commodities for consumption. The municipality of Man-daon becomes more and more progressive, and the increasing number of big establishments has been described as a threat to the SME's day-to-day activities. Therefore, this study empha-sized SMEs rather than big establishments. To address this problem, researchers evaluated the profound impact of big es-tablishments on small and medium enterprises (SMEs) in Ba-rangay Poblacion, Mandaon, Masbate. The data from the aforementioned situation and problem were gathered through a survey utilizing a self-made Likert-scale questionnaire, which was then evaluated by reliability testing using SPSS statistics. The reliability statistics indicate that the high Cronbach's alpha value of.987 suggests very strong internal consistency among the items in the scale. It was distributed to 50 respondents, who are small and medium enterprises (SMEs) that were chosen through a purposive sampling design. The findings of the study show that the existence of big establishments has an adverse impact on the operation of small and medium enterprises (SMEs). Based on the analysis of the data, the monthly sales, revenue, and pricing of SMEs were affected. In addition, the customers were highly affected by the opening of the big estab-lishment, and the results were analyzed through weighted mean and multivariate analysis. As a result, the researchers will recommend a comprehensive capacity building activity entitled GROW-ME: Generating Revenue Opportunities for Well-Managed Enterprises. it is an innovative extension activity, of-fering training program, workshop and mentorship opportunity to implement various development strategies. This initiative is designed to enhance the skills and capabilities of SME owners and employees. Minimizing the influence of big establishments on SME’s can be crucial for fostering a competitive and diverse business environment.